Melatonin pathway transmits information to terminate pupal diapause in the Chinese oak silkmoth Antheraea pernyi and through reciprocated inhibition of dopamine pathway functions as a photoperiodic counter. Issue 1 (16th February 2014) - Wang, Qiushi; Egi, Yuichi; Takeda, Makio; Oishi, Katsutaka; Sakamoto, Katsuhiko
Abstract The present study investigated the functional involvement of melatonin and dopamine in photoperiodism to terminate pupal diapause in the Chinese oak silkmoth, Antheraea pernyi (Lepidoptera: Saturniidae). Diapause in this long‐day (short‐night) species is maintained during long nights and can be terminated by exposure to a short‐night photoperiod. We observed the effects of melatonin and dopamine and their receptor antagonists on diapause pupae. Melatonin and flupentixol, a dopamine receptor antagonist, terminated pupal diapause even under long‐night photoperiods. Dopamine and luzindole, a melatonin receptor antagonist, retarded adult emergence during short nights, whereas melatonin advanced the timing of adult emergence under the short‐night photoperiod in a manner dependent on the number of injections. The results of the day‐length extension experiment indicated that a change in the photoperiod was immediately detected as mRNA expression of the rate‐limiting enzyme of melatonin production. These findings suggest that the melatonin pathway transmits information on the photoperiod to terminate the pupal diapause of A. pernyi. The melatonin pathway also inhibited the dopamine production system, and the dopamine pathway inhibited the melatonin production system. We propose an insect model of the photoperiodic counter driven by mutual inhibition between the melatonin and dopamine pathways.